Adaptation and validation of psychological capital questionnaire: An Indonesian version - Maulida Nurul Fatimah; Rosita Endang Kusmaryani (Psychology, Evaluation, and Technology in Educational Research, 2026)
Psychological capital is a positive psychological resource that enables individuals to stay optimistic, resilient, and confident when facing challenges. However, valid and reliable instruments to measure psychological capital in Indonesia remain limited, creating a gap in local assessment. Therefore, this study aimed to adapt and validate the Indonesian version of the Psychological Capital Questionnaire (PCQ-24) to ensure linguistic and psychometric equivalence. The research employed a quantitative design with both qualitative and quantitative analyses. The adaptation process followed stages of translation, synthesis, back translation, expert review, and pilot testing. Qualitative analysis was conducted to assess item equivalence and cultural appropriateness, while quantitative analysis involved Confirmatory Factor Analysis (CFA) and reliability testing. The participants were 202 Generation Z employees aged 20-28 years selected using purposive sampling. The adaptation produced 24 linguistically equivalent items after minor revisions. CFA confirmed a four-factor model hope, efficacy, resilience, and optimism with acceptable fit indices (CFI = 0.830; RMSEA = 0.073; SRMR = 0.068) and reliability ranging from 0.60-0.77 (overall = 0.996). These findings indicate that the Indonesian PCQ-24 is linguistically appropriate and psychometrically reliable for measuring psychological capital among Generation Z employees.